Hukum Bayi Tabung Dalam Perspektif Hukum Islam Kontemporer - Yannur Rezkina Harahap; Nazwa Fadillah Ritonga; Unzurnaa; Salsabila Fitri Anggraini; Rojaya Marbun (Albayan Journal of Islam and Muslim Societies, 2024)
This study examines the Islamic Legal Perspective on in vitro vertilization (IVF), commonly known as test – tube baby procedures, which serve as a medical solution for married couples facing infertility, The research focuses on the permissibility and boundaries of IVF according to islamic principles, such as lineage vlarity, prohibition of adultery, and preservation of progeny (hifz al-nasl). Anormative qualitative method with a descriptive-analytical approach is used, based on the Qur’an, Hadith, and Contemporary scholars’ opinions. The findigs indicate that IVF is permissible in islam as long as the sperm and ovum originate from a legally married couple, and the fertilization process does not involve third parties such a sperm or egg donors or surrogate mothers. Involving third parties renders the procedure impermissible due to the risk of lineage confusion and violation of marital principles. Thus, the permissibility